Heart rate, heart rhythm and prognostic benefits of beta-blockers in heart failure: individual patient-data meta-analysis - Kotecha, D; Flather, M; Altman, D; Holmes, J; Rosano, G; Wikstrand, J; Packer, M; Coats, A; Manzano, L; Böhm, M; van Veldhuisen, D; Andersson, B; et al. (Elsevier, 2017)
Meta-analysis of individual-patient data from eleven double-blind randomized trials found that higher baseline heart rate was associated with greater all-cause mortality for those in sinus rhythm, but not for those in AF. Mortality was lower for patients in sinus rhythm assigned beta-blockers (HR 0.73, 95% CI 0.67-0.79; p<0.001), regardless of baseline heart rate. Beta-blockers had no effect on mortality in patients with AF (HR 0.96, 95% CI 0.81-1.12; p=0.58) at any heart rate. A lower achieved resting heart rate was associated with better prognosis only for patients in sinus rhythm (HR 1.16 per 10 beats/minute increase, 95% CI 1.11-1.22; p<0.0001).